Socialization of the General Election Commission's Continuous Voter Data Update Program: Sosialisasi Program Pemutakhiran Data Pemilih Berkelanjutan Komisi Pemilihan Umum - Pujianto, Bambang; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine, analyze the socialization of the continuous voter data updating program of the General Election Commission of Sidoarjo Regency. Qualitative descriptive research methods and data collection techniques through interviews, observation and documentation. Determination of informants is done by purposive sampling method. Data analysis techniques through data collection, data reduction, data presentation, drawing conclusions. The results of this study indicate that the socialization of the continuous voter data updating program of the General Election Commission of Sidoarjo Regency is by direct and indirect socialization. Direct socialization was carried out with the OPD regarding the ongoing voter data updating program of the General Election Commission of Sidoarjo Regency and carried out socialization in high schools (SMA) in Sidoarjo Regency. Meanwhile, indirect socialization is carried out using social media owned by the General Election Commission of Sidoarjo Regency.